2006
DOI: 10.1115/1.2720505
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Unsteady Flow Field in a Vaned Diffuser of a Transonic Centrifugal Compressor

Abstract: Transonic centrifugal compressors are used with high-load turbochargers and turboshaft engines. These compressors usually have a vaned diffuser to increase the efficiency and the pressure ratio. To improve the performance of such a centrifugal compressor, it is required to optimize not only the impeller but also the diffuser. However the flow field of the diffuser is quite complex and unsteady because of the impeller located upstream. Although some research on vaned diffusers has been published, the diffuser f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Whether the diffuser can be studied in isolation from the impeller has been the subject of much research. It is now firmly established that the unsteadiness resulting from the jet-wake impeller exit flow persists through the diffuser (see, for example, [19,20]). However, it has been suggested, using both numeric analysis and careful experimentation, that the effects of unsteadiness on the diffuser flow are small relative to the effects of the time-mean spanwise flow non-uniformity in the impeller exit flow [21][22][23].…”
Section: Approachmentioning
confidence: 99%
“…Whether the diffuser can be studied in isolation from the impeller has been the subject of much research. It is now firmly established that the unsteadiness resulting from the jet-wake impeller exit flow persists through the diffuser (see, for example, [19,20]). However, it has been suggested, using both numeric analysis and careful experimentation, that the effects of unsteadiness on the diffuser flow are small relative to the effects of the time-mean spanwise flow non-uniformity in the impeller exit flow [21][22][23].…”
Section: Approachmentioning
confidence: 99%
“…Ibaraki et al 3 measured the meridional velocity distributions at different crosssections along a transonic impeller chord to reveal the loss generation mechanism of the impeller flow using the Laser Doppler Velocimetry (LDV) technique. Ibaraki et al 4 applied particle image velocimetry (PIV) to measure the flow characteristics inside a vaned diffuser. This suggests that the impeller wake still exists downstream toward the diffuser throat and continues to mix in the spanwise direction.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained by him show that the flow in the impeller and volute casing is periodically unsteady and confirm the circumferential distortion of the pressure distribution at the impeller outlet and in the volute casing. Ibaraki et al [16] in their work have found that a complex three-dimensional flow with distortion between the shroud and the hub is observed.…”
Section: Introductionmentioning
confidence: 96%
“…A host of articles [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] is available which explicitly explore the impeller diffuser interactive phenomenon by both experimental and numerical methods.…”
Section: Introductionmentioning
confidence: 99%